Social Media Analysis Of The Purchase Decision Of Kenangan Coffee Among Gen Z in Surabaya City - Lailatul Fitri Dwi Rahmawati; Ety Dwi Susanti (Lavish Opulent Education, 2025)
The rapid growth of the coffee industry in Indonesia, driven by Gen Z and social media, is the background to this research. This study analyzes the influence of social media on purchasing decisions for Kopi Kenangan among Generation Z in Surabaya. The focus is on identifying purchasing drivers, Kopi Kenangan's content strategy, and its effectiveness. The results show that Kopi Kenangan's product significantly influences social media and purchasing decisions. Social media also proved significant in influencing purchasing decisions. Interestingly, price and content did not have a significant direct influence, but social media played a significant role as a mediator between the product and purchasing decisions